2014
DOI: 10.1039/c3cc45025b
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic hydrogen production from a noble metal free system based on a water soluble porphyrin derivative and a cobaloxime catalyst

Abstract: A combination of noble-metal free components, a water soluble porphyrin photosensitizer zinc meso-tetrakis(1-methylpyridinium-4-yl)porphyrin chloride [ZnTMPyP(4+)]Cl4 (1) with cobaloxime complex [Co(III)(dmgH)2(py)Cl] (2) as a catalyst, creates an efficient system for photochemical hydrogen production acting under visible light with 280 TONs. This is the first example of a water soluble porphyrin acting as a photosensitizer for cobaloxime catalysed H2 production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
93
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 25 publications
4
93
1
Order By: Relevance
“…Exemplarily, significant efforts have been reported applying cobalt and nickel complexes as proton reduction catalysts (WRC) (Although the term "water reduction catalyst" as well as the related abbreviation WRC is commonly used in relevant literature it should be named proton reduction catalyst in the strict sense) [30][31][32][33][34][35][36][37][38][39][40]. For example, various groups investigated cobaloxime-based catalysts [25,31]. Recently, these systems have been outperformed by pentapyridyl cobalt complexes achieving a turnover number (TON) with respect to Co of up to 11,000 with a Re-photosensitizer (PS) and ascorbic acid (SR) [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exemplarily, significant efforts have been reported applying cobalt and nickel complexes as proton reduction catalysts (WRC) (Although the term "water reduction catalyst" as well as the related abbreviation WRC is commonly used in relevant literature it should be named proton reduction catalyst in the strict sense) [30][31][32][33][34][35][36][37][38][39][40]. For example, various groups investigated cobaloxime-based catalysts [25,31]. Recently, these systems have been outperformed by pentapyridyl cobalt complexes achieving a turnover number (TON) with respect to Co of up to 11,000 with a Re-photosensitizer (PS) and ascorbic acid (SR) [36].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, especially ruthenium complexes have played a key role since the 1970s [68][69][70][71][72][73][74], later followed by various iridium [75,76], platinum [77][78][79] and rhenium [80][81][82][83][84][85] complexes. In contrast, more abundant metals or even metal-free photocatalytic systems were reported: examples include, e.g., iron [86], zinc [24,25,[87][88][89] and magnesium-based [24,[90][91][92][93][94] photosensitizers, CdTe [95], CdSe [39] or carbon [96] quantum dots or organic dyes [38][39][40][97][98][99][100][101][102][103][104] together with either cobalt or nickel catalysts. Mostly, the reported activities and stabilities were still low.…”
mentioning
confidence: 99%
“…[9] To make a water splitting system commercially viable, these rare and expensive noble metals should be replaced by cheaper and more abundant materials, as was already demonstrated in the case of Eosin Y, [10] fluorescein, [11] Al-, [12] Zn- [13] and Sn-porphyrins [14] as well as quantum dots. [15] Copper based chromophores, in particular copper(I) bis-1,10-phenanthroline complexes represent another very attractive alternative.…”
Section: Introductionmentioning
confidence: 99%
“…5 15,16 and sometimes also ascorbate as electron source, 16 which is rather easily oxidized (E~+0.3 V 23 ) and thus the energy gain of the photoreaction is rather small.…”
Section: Introductionmentioning
confidence: 99%
“…However, we observed that this combination of compounds evolves H 2 rather slowly and rates are clearly lower than for our previously reported Re/Co or Sn/Pt systems operated at the same conditions. [18][19][20][21] It also fails to reach anywhere near the reaction rates or turnover numbers of the recently reported combinations of Zn/Al-porphyrins with [Co(dmgH) 2 ]-type catalysts 15,16 and so it is obvious that the combined disadvantageous effects of catalyst instability (Co), short excited-state lifetime (porphyrin in H 2 O) and demanding oxidation potential of the electron source (TEOA) make this reaction chain far from ideal. UV/Vis spectroscopy.…”
Section: Introductionmentioning
confidence: 99%